Development of INoSIT (Integration Nature of Science in Inquiry with Technology) Learning Models to Improve Science Literacy: A Preliminary studies - Amiruddin Takda; Budi Jadmiko; Erman Erman (Postgraduate, University of Mataram, 2022)
Has successfully created the INoSIT learning paradigm to increase students' science literacy competency. This design aims to integrate information and communication technology (ICT) with inquiry and nature of science (NoS) models to teach scientific literacy to junior high school students using a multi-representation method. The BSCS 5E model (Involvement of Biological Science Curriculum Study, Exploration, Explanation, Elaboration, and Evaluation) and the IBL model (Investigation-based learning) have many phases whose implementation requires many processes. So, the INoSIT model is designed to simplify multiple phases or sub-phases. As a result, IBL (inquiry-based learning) is ineffective and inefficient in terms of learning time. It is also challenging to teach scientific literacy of abstract concepts using this method. The study employs a descriptive analysis method in conjunction with a literature review pattern.Â The INoSIT model with the syntax Eliciting, Hypothesis, Testing Hypothesis, Elucidation, and Reflection was created from the results of the investigation of the weaknesses of the BSCS 5E (Biological Science Curriculum Study Engagement, Exploration, Explanation, Elaboration, and Evaluation) and the IBL (Inquiry-based learning) models. To construct students' knowledge of literacy and the study is anticipated to contribute to creativity, originality, and the development of a proclivity for inquiry and research